2019
DOI: 10.1124/jpet.119.258178
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of Ranolazine versus Common Cardiovascular Drugs in Patients with Early Diastolic Dysfunction Induced by Anthracyclines or Nonanthracycline Chemotherapeutics: A Phase 2b Minitrial

Abstract: We have reported that anthracyclines and nonanthracycline chemotherapeutics caused diastolic dysfunction in cancer patients without cardiovascular risk factors. Diastolic dysfunction occurred as early as 1 week after the last chemotherapy cycle and manifested as impaired myocardial relaxation at echocardiography or persistent elevations of B-type natriuretic peptide (BNP) or troponin. The antianginal drug ranolazine shows cardiac relaxant effects that we considered of value to treat early diastolic dysfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…[26][27][28] One study targeted type 2 diabetes patients with HF syndrome. 29,30 Another study recruited patients with hypertrophic cardiomyopathy with a left ventricular thickness of 15 mm. 31 A more detailed description of study characteristics is attached in Supplementary Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…[26][27][28] One study targeted type 2 diabetes patients with HF syndrome. 29,30 Another study recruited patients with hypertrophic cardiomyopathy with a left ventricular thickness of 15 mm. 31 A more detailed description of study characteristics is attached in Supplementary Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…To our knowledge, the efficacy and safety of ranolazine or other Na v channel blockers in oncology have not been assessed in clinical trials. However, ranolazine may reduce the cardiotoxicity of anticancer therapy (trastuzumab, doxorubicin) in mice, thus paving the way to a clinical trial [138,[202][203][204]. A controlled trial is needed regarding the potential of ranolazine on relieving chemotherapy-related diastolic dysfunction and its safety profile in cancer patients compared to that of the general population [204].…”
Section: Ranolazine and Cancermentioning
confidence: 99%
“…Conversely, although mean BNP/NT‐proBNP levels were increased in patients post‐cancer therapy, these biomarkers did not consistently predict LV dysfunction (OR 1.7, 95% CI 0.7–4.2). It was recently suggested that post‐cancer therapy elevations of NT‐proBNP might herald early diastolic dysfunction rather than LV systolic dysfunction 82 …”
Section: Early Diagnosis Of Cardiotoxicitiesmentioning
confidence: 99%
“…It was recently suggested that post-cancer therapy elevations of NT-proBNP might herald early diastolic dysfunction rather than LV systolic dysfunction. 82 Troponin elevation was also useful to monitor the efficacy of preventive therapy, with lower levels seen with angiotensin-converting enzyme (ACE) inhibitor or angiotensin II receptor blocker (ARB) therapy (OR 9.8, 95% CI 2.6-37.1) and, to a lesser extent, beta-blocker therapy (OR 2.1, 95% CI 1.3-3.6). 81 However, a multicentre prospective study, the International CardioOncology Society (ICOS)-one trial, did not demonstrate prevention of troponin elevations by ACE inhibitor therapy, 83 84 and Carvedilol Effect in Preventing Chemotherapy-Induced Cardiotoxicity (CECCY) 85 trials demonstrated an attenuation of the troponin response to anthracycline therapy by beta-blocker therapy.…”
Section: Biomarkersmentioning
confidence: 99%